Propuesta de un plan estratégico institucional para el gobierno autónomo descentralizado municipal del cantón Logroño, provincia de Morona Santiago, período 2016 - 2020. - Ruiz Cabrera, Renelda Gabriela (2018)
The main purpose of the present project is to prepare an Institutional Strategic Plan for the Municipal Autonomous Decentralized Government of the Logrono Canton, Province of Morona Santiago, for the period 2016- 2020, which allows determining the institutional objectives, defining strategies and actions to be they will execute to reach them in the entity. For the fulfillment of the general objective and specific objectives, the methodology was used which includes several methods and techniques, of which stand out: inductive method, deductive method, historical method, descriptive method, synthetic method and the statistical method, as well as the use of techniques such as: the interview, the survey. For the elaboration of the Strategic Plan the following procedure was fulfilled according to the specific objectives, in this way the internal and external context of the entity was diagnosed to determine the (SWOT) strengths, Opportunities, Weaknesses and Threats, through an interview conducted to the Lord Mayor and 110 officials ;, as well as the execution of surveys to 282 users whose information allowed to establish the proposal. Therefore, among the strengths were found such: Management aligned a development plan, annual operating plan and budget, existence of an institutional organization chart, it has an excellent work environment, punctuality in the payment of salaries to employees, it has adequate technology to execute the service, predisposition and adaptability to change. Also among the weaknesses can be noted: outdated institutional philosophy, there is no training plan for officials, it lacks a manual of functions and processes, making vertical decisions, the integration processes are not executed, motivation, formal communication and supervision, staff performance evaluation is not executed and compliance indicators are not applied. In the MEFI matrix, a weighted value of 2.49 is determined and in the MEFE matrix of 2.72. Likewise, the SWOT matrix and the high impact matrix are structured, from which the objectives originate. strategic, that the organization must put in place to achieve the desired objectives. Likewise, it was possible to find different GADML objectives such as: Procure the welfare of the community and contribute to the promotion and protection of local interests, plan and promote the physical development of the canton and its urban and rural areas, increase the spirit of integration of all social and economic actors, citizenship and the confraternity of the population to achieve the growth and progress of the canton, coordinate with other entities, the development and management of culture, education and social assistance, research, analyze and recommend most appropriate solutions to the problems faced by the Municipal Government, with adjustments to changing conditions, socially, politically and economically, to study the municipal theme and recommend the adoption of rationalized and business management techniques, with uniform and flexible work procedures , tending to professionalize and specialize the management of local government, auspic promote and promote the holding of permanent meetings to discuss municipal problems, through the use of round tables, seminars, workshops, conferences, symposiums, courses and other integration and work activities, training of human resources, aimed at professionalizing municipal management. The conclusions of the research work have their respective recommendation, which highlights the most important results of the investigation, in order for the Mayor to take the necessary corrective measures for the benefit of the Municipal GAD of the Logroño canton.